Improving Descriptive Writing Skills Through the Implementation of the Jigsaw Cooperative Learning Model in Grade IX Students at SMP Negeri 4 Karau Kuala, South Barito Regency - Franciska, Eva Lesiani; Nurhidayah, Nurhidayah (Journal of Educational Sciences, 2026)
Writing descriptive texts is a fundamental component of Indonesian language learning at the junior secondary level; however, many students still experience difficulties in organizing ideas, selecting appropriate vocabulary, and constructing coherent paragraphs. This study aimed to improve both the learning process and students’ descriptive writing skills through the implementation of the Jigsaw cooperative learning model in Grade IX students at SMP Negeri 4 Karau Kuala, South Barito Regency. The research employed a Classroom Action Research design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 25 ninth-grade students, and the research was carried out collaboratively with the Indonesian language teacher. Data were collected through observation sheets, questionnaires, interviews, written tests, and documentation, and were analyzed using descriptive qualitative analysis supported by quantitative data. The results indicated that the implementation of the Jigsaw cooperative learning model improved student engagement, collaboration, and motivation during the learning process. In addition, students’ descriptive writing skills showed consistent improvement across cycles in terms of content, organization, grammar, language style, and writing mechanics. The study concludes that the Jigsaw cooperative learning model is effective in enhancing descriptive writing skills and creating a more active and meaningful learning environment.